Energy Efficiency of â€œGreen Structuresâ€ in Cooling Period - Tetiana, Tkachenko; ., . (International Journal of Engineering and Technology, 2018)
The proposed methodology for estimating the reduction of CO2 emissions by green constructions (green roof and facade greening) due to the â€œcooling effectâ€ during the cooling period allows to calculate CO2 savings in warm periods of the year. For Kyiv, in July, the reduction of CO2 emissions per m2 at coal using is 133Â gÂ /Â m2, during the warm period of the year â€“ 515Â gÂ /Â m2; using gas â€“ 78Â gÂ /Â m2 and 303Â gÂ /Â m2. It is established that the energy savings of a green roof depends on the thickness of the thermal insulation of buildings: the thicker insulation causes the less green roof contribution to energy savings. However, the significance of their effectiveness remains. Green roofs can be especially effective in switching from gas to local solid fuels: peat waste, pellets, etc. As a practical recommendation, it is proposed to coordinate the placement of greened and ungreen parts of the green roof with rooms under the roof, which allows to reduce the refrigeration load on air conditioning. In addition, recommendations on grass care on the green roof have been developed. To maximize the cooling effect, it is necessary to maintain grass height no more than120 mm. Before the beginning of the transition period, it is necessary to stop mowing the grass, which reduces the cooling effect.Â Â